Dampak Ahlusunnah Wal Jamaah terhadap Masyarakat Desa Ngreco Kecamatan Kandat Kabupaten Kediri - Agus Miftakus Surur; M. Syahrul Munir (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
The Sunnis known as the ahlussunnah wal jama'ah refers to one of the four Islamic schools of Hanafi, Maliki, Syafi'i, and Hambali in implementing their religious rituals. They also adhere to the pro- visions of Abu Hasan Al Asy'ari and Imam Al Maturidi in the field of aqeedah. As a great ulama who had meritorious raising the flag of ahlussunnah wal jama'ah and declaring himself to be out of the Mu'tazilites. The teachings of ahlussunnah wal jama'ah are admitted to widely change society due to its teaching styles thatare easily in- terpreted by Muslims. In addition, their thoughts about the nature of God, human actions, deeds of God, anthropomorphism, God remem- brance, God revelation, and the reason can be universally accept- ed among society. Regarding to the role ofahlussunnah wal JamaÃ¡h school in Muslims, this research is descriptive and practical by using an inductive approach. The process and meaning of the subjects view are more highlighted. Relevanttheories are chosen as a basis and ref- erence for research. The research results reveal that the community of ahlussunnah wal jama'ah at the Ngreco village always under pintheir religious activities by the spirit of ahlussunnah wal jama'ah which has greatly influenced the lives of people and humans in the world for the hereafter.